2022
DOI: 10.1177/09730052221107730
|View full text |Cite
|
Sign up to set email alerts
|

Farmer Producer Organisations in North India: Potentials and Challenges

Abstract: This article seeks to analyse the current business model of FPOs to understand socio-economic consequences for individual members. The study selected 10 farmer producer organisations from Uttar Pradesh, India considering diversity along with geographical location, the field of operation and business model. In total, 10% of the villages covered by each chosen FPO and 5 members from each selected village were randomly selected for data collection. Two separate schedules for FPOs and members were administered for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…During the growth phase of FPOs, many studies have found that working capital is a big challenge for these FPOs [63] . One of the most common problems stated in many studies is the lack of funds and support for the FPOs [64,65] . This phenomenon can also be confirmed in the study conducted by Neti et al [10] that the median paid-up capital per producer company in India is only Rs.…”
Section: Discussionmentioning
confidence: 99%
“…During the growth phase of FPOs, many studies have found that working capital is a big challenge for these FPOs [63] . One of the most common problems stated in many studies is the lack of funds and support for the FPOs [64,65] . This phenomenon can also be confirmed in the study conducted by Neti et al [10] that the median paid-up capital per producer company in India is only Rs.…”
Section: Discussionmentioning
confidence: 99%
“…The above review shows that these are mostly individual PC case studies of impact or those with only member farmer based assessment. There are others which only assess financial performance of PCs (Singh & Singh, 2014; Kakati & Roy, 2021; Mourya & Mehta, 2021; Trivedi et al., 2022) or report just PC Board members’ and CEOs’ perceptions based analysis of member impact or benefits (Deka et al., 2020; Mourya & Mehta, 2021), or those which only examine a single or a few PCs for impact on member farmers as compared with that on the non‐member farmers (Lalitha et al., 2022; Mukherjee et al., 2022). Some others attribute all gains from the sale of agricultural commodities by the member farmer households to the PCs (Trivedi et al., 2022).…”
Section: Review Of Previous Studies and Rationale For The Studymentioning
confidence: 99%
“…There are others which only assess financial performance of PCs (Singh & Singh, 2014; Kakati & Roy, 2021; Mourya & Mehta, 2021; Trivedi et al., 2022) or report just PC Board members’ and CEOs’ perceptions based analysis of member impact or benefits (Deka et al., 2020; Mourya & Mehta, 2021), or those which only examine a single or a few PCs for impact on member farmers as compared with that on the non‐member farmers (Lalitha et al., 2022; Mukherjee et al., 2022). Some others attribute all gains from the sale of agricultural commodities by the member farmer households to the PCs (Trivedi et al., 2022). Some others claim to have surveyed both the members and the non‐members but report only the member farmer data based impact on income or cropping pattern where the members’ net annual income went up by 16% and the area under high value crops such as pulses or vegetables expanded and those of food crops such as paddy or wheat declined after the membership of the Farmer Producer Organizations (FPOs) in Punjab (Renuka & Singh, 2021).…”
Section: Review Of Previous Studies and Rationale For The Studymentioning
confidence: 99%
“…FPOs sometimes face competition among themselves and with other agricultural marketing channels, and coordination issues can arise, leading to inefficiencies in the sector. FPOs often focus on a single crop or a few crops [7][8][9][10]. This can lead to issues when dealing with crop failures or market fluctuations.…”
Section: Introductionmentioning
confidence: 99%